Drug-induced osteonecrosis of the jaw: the state of the art - A. Fassio; F. Bertoldo; L. Idolazzi; O. Viapiana; M. Rossini; D. Gatti (PAGEPress Publications, 2017)
Osteonecrosis of the jaw (ONJ) is a rare adverse event of antiresorptive drugs such as bisphosphonates (BP) and denosumab (DMAb). The diagnosis of ONJ is considered in cases where exposed bone in the maxillofacial region does not heal within 8 weeks in a patient previously treated with an antiresorptive agent. In patients with osteoporosis, ONJ is reported as a very rare adverse event while in oncologic patients with bone metastases or malignant hypercalcemia the incidence is significantly higher (up to the 1-10% of the patients). The pathophysiology of ONJ is still not completely understood but it is multi-factorial. ONJ is a condition associated with poor oral health, oral surgery, and use of antiresorptive agents. Prevention is of paramount importance especially in cancer patients, in whom the large majority of cases of ONJ (>90%) are reported, but it should also be considered in osteoporotic patients, especially during dental surgical procedure. Some simple prevention procedures are effective in reducing the risk of its appearance. When ONJ unfortunately occurs, the large majority of patients can be managed conservatively. In conclusion, ONJ is a rare condition associated with antiresorptive drugs. Both osteoporotic and oncologic patients should be well informed about its low absolute risk and regarding the fact that the benefits of antiresorptive therapy far outweigh this potential risk of ONJ.